Towards human rabies elimination in Eastern Europe and Middle East: current status and prospects (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Following the 1st Middle East and Eastern Europe Rabies Expert Bureau (MEEREB) meeting held in Turkey in 2010, the group of rabies experts from 8 participating countries met in June 2012 in Paris, France for the 2nd meeting, together with representatives from the Institute Pasteur and the Global Alliance for Rabies Control to discuss the rabies situation in their respective countries, its evolution, the problems encountered and the solutions. Human rabies, number of animal bites and post-exposure prophylaxis (PEP) administered are notifiable in all MEEREB countries however reliable rabies data in the region still remain scarce especially regarding human rabies reporting. This is even more pronounced in countries that are not part of the Rabies Bulletin Europe. Thanks however to MEEREB members’ active participation, a clearer image of the rabies situation in the region is becoming more apparent. Some of MEEREB countries (Croatia and Serbia) have not recorded human deaths from rabies for more than 30 years. However, persistence of rabies in wildlife (foxes) requires constant surveillance and maintenance of a high level of vigilance and public health interventions in order to prevent human rabies cases. In other MEEREB countries rabies is present not only in wildlife but also in dogs, which increases the risk of transmission to humans. In fact, human cases still do occur in these countries. In countries where the incidence of human rabies did not exceed 0.15 per million inhabitants during the last 3 years, the incidence of reported bites and PEP remained stable. In the two countries where the incidence of human rabies is the highest, Kazakhstan and Georgia (0.38-0.52 and 0.67-1.37, respectively), the mean PEP incidence increase rate was of over 15%. In 2011, 0.4% of Kazakh population received PEP. In Georgia, PEP incidence reached 0.9% – the highest known PEP incidence in the world, and 2-50 fold higher than in other MEEREB countries. All MEEREB countries use cell culture vaccines through intramuscular administration. Rabies immunoglobulin (RIG) is locally produced in Croatia, Serbia, and Ukraine. MEEREB participants stated that human rabies transmitted by dogs can be and should be eliminated from the region and discussed requirements to conduct a successful rabies elimination program. Although in all MEEREB countries a legal framework for rabies control exists, most often rabies elimination is not considered as a public health priority. In addition, although some rabies control measures are already in place, there is still a significant disparity among the MEEREB countries as to each country’s response to its rabies situation. Furthermore, some of the conditions for successful rabies elimination programs are not met. MEEREB members agreed that reinforced intersectional collaboration and “One Health approach” are the keys for successful rabies control.